(3QSGdI GdaQOhS aj eGgjI GdEfSGf hghjJg hCQcGfg heG Sjchf Ydjg HYO eaGQbI GdQhMs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdCehQ GdehLhOI ajfG dcd efgG eGgjI hghjI GdN s
(3Vef eLehY , JQJjHgG (B: (3ef U (B53 - (3U(B60s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B7 - (3U (B210 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3adSaI (B808) s
Keywords: (3GdadSaI hGdefWbs